Design, construction and evaluation of an animal drawn disc harrow - Usman, A.M.; Haque, M.A.; Umar, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
Animal traction has not been widely adopted by Nigerian farmers despite the fact that it is an appropriate technology that can be used to increase agricultural production. One of the reasons for limited use of animal power is the lack of appropriate implements. The objective of this work was, therefore, to design, construct and evaluate a single-acting animal-drawn disc harrow. The harrow consisted of several components fastened together into a unit which could be easily dismantled if necessary. The main parts were the frame; two gangs of four discs each, three pneumatic depth control wheels and a seat for the operator. The total mass of the implement was found to be 100 kg. A pair of well trained bulls weighing 429 kg and 394 kg where used to pull the implement during the experiment.The harrow was designed to operate at various depths and disc angles. The draught measurements and quality of work of the harrow were observed at depths of 5 and 10 cm and disc angles of 15o, 25o and 35o. It was found that the harrow had a draught of 530 N when set at a disc angle of 15o and depth of 5 cm, and 778 N when set at 35o and 10 cm depth. It was also found that the harrow had 94.76% weed destruction when set at disc angle of 15o and depth of 5 cm and 97.90% when set at 35o disc angle, 10 cm depth of operation. The harrow was found to have an effective field capacity of 0.23 ha/h and field efficiency of 86 %.